Search for Associated W and Higgs Boson Production in p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Rijssenbeek, M.; et al. (Amer Physical Soc, 2009)
We present results of a search for WH -> l nu b (b) over bar production in p (p) over bar collisions based on the analysis of 1.05 fb(-1) of data collected by the D0 experiment at the Fermilab Tevatron, using a neural network for separating the signal from backgrounds. No signal-like excess is observed, and we set 95% C. L. upper limits on the WH production cross section multiplied by the branching ratio for H -> b (b) over bar for Higgs boson masses between 100 and 150 GeV. For a mass of 115 GeV, we obtain an observed (expected) limit of 1.5 (1.4) pb, a factor of 11.4 (10.7) times larger than the standard model prediction.